Answer: 5
=========================================================
Step-by-step explanation:
Vertex form is
y = a(x-h)^2 + k
We are told the vertex is (3,-2), so we know (h,k) = (3,-2)
y = a(x-h)^2 + k will update to y = a(x-3)^2 - 2
--------
Then we also know that (x,y) = (4,3) is a point on the parabola. Plug those x and y values into the equation and solve for 'a'
y = a(x-3)^2 - 2
3 = a(4-3)^2 - 2
3 = a(1)^2 - 2
3 = a - 2
3+2 = a
5 = a
a = 5
This is the coefficient of the x^2 term since the standard form is y = ax^2+bx+c.